Sulconazole inhibits PD-1 expression in immune cells and cancer cells malignant phenotype through NF-κB and calcium activity repression - Pernot, Simon; Tomé, Mercedes; Galeano-Otero, Isabel; Evrard, Serge; Badiola, Iker; Delom, Frederic; Fessart, Delphine; Smani, Tarik; Siegfried, Geraldine; Villoutreix, Bruno O.; Khatib, Abdel-Majid (Frontiers in Immunology, 2024)
The overexpression of the immunoinhibitory receptor programmed death-1 (PD1) on T-cells is involved in immune evasion in cancer. The use of anti-PD-1/PDL-1 strategy has deeply changed the therapies of cancers and patient survival. However, their efficacy diverges greatly along with tumor type and patient populations. Thereby, novel treatments are needed to interfere with the anti-tumoral immune responses and propose an adjunct therapy. In the current study, we found that the antifungal drug Sulconazole (SCZ) inhibits PD-1 expression on activated PBMCs and T cells at the RNA and protein levels. SCZ repressed NF-κB and calcium signaling, both, involved in the induction of PD-1.Further analysis revealed cancer cells treatment with SCZ inhibited their proliferation, and migration and ability to mediate tumor growth in zebrafish embryos. SCZ found also to inhibit calcium mobilization in cancer cells. These results suggest the SCZ therapeutic potential used alone or as adjunct strategy to prevent T-cell exhaustion and promotes cancer cell malignant phenotype repression in order to improve tumor eradication.